2020
DOI: 10.1111/ene.14253
|View full text |Cite|
|
Sign up to set email alerts
|

Trimethylamine‐N‐oxide is elevated in the acute phase after ischaemic stroke and decreases within the first days

Abstract: Background and purpose Trimethylamine‐N‐oxide (TMAO) is a biomarker of the gut microbiome and correlates with the risk of cardiovascular diseases. However, conflicting data exist on the specific role of TMAO in ischaemic stroke patients. We aimed to analyze the time course of TMAO levels in stroke patients compared with controls. Methods In this prospective, case‐control study, patients suffering from ischaemic stroke (onset <24 h) and control patients with less than two cardiovascular risk factors were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 30 publications
7
27
0
Order By: Relevance
“…Our results are in line with a recent study (7), which included 296 patients (196 patients with ischemic stroke and 100 patients with a low cardiovascular risk profile). TMAO levels were significantly higher in stroke patients compared to controls, but there was no difference between patients with different stroke etiologies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in line with a recent study (7), which included 296 patients (196 patients with ischemic stroke and 100 patients with a low cardiovascular risk profile). TMAO levels were significantly higher in stroke patients compared to controls, but there was no difference between patients with different stroke etiologies.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the number of patients is relatively small as we set out to obtain the plasma sample of patients immediately on admission in the emergency room. Previous studies have shown that the timing of TMAO measurement is paramount (7,17). We do not have any follow-up data on the patients with asymptomatic cerebrovascular atherosclerosis, so that we cannot answer the question, whether TMAO would predict future cerebrovascular events.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…TMAO was measured using electrospray ionization tandem mass spectrometry according to a modified protocol of Wang et al [4] . The modifications are described by Schneider et al [4] .…”
Section: Methodsmentioning
confidence: 99%
“…TMAO was measured using electrospray ionization tandem mass spectrometry according to a modified protocol of Wang et al [4] . The modifications are described by Schneider et al [4] . In brief, plasma samples were prepared according to Wang et al with minor modifications: 10 µL samples were pipeted into a 1.5 ml centrifuge tube.…”
Section: Methodsmentioning
confidence: 99%